Varianty pristavocnykh glagolov nesoversennogo vida v Russkom jazyke : Variants of Russian prefixed imperfectives - Pols, Adriana (Language and Linguistics - Book Archive pre-2000, 1993)
This study examines the correlation between form and meaning of Russian prefixed imperfective verbs ending in -át'/-ját' and -yvat'/-ivat' which are derived from one and the same root (-gotóvit', podgotovlját'/podgotávlivat'). The following questions are discussed: Which factors determine the use of either the form -át' or the form in -yvat'? What is the role of the opposition determinate/indeterminate in verbs which do not express linear motion? What is the relation between prefix and suffix? (-xvalit', vosxvalját', vyxvalját'/vyxválivat', naxválivat').Is there a tendency for forms in -át' to be replaced by forms in -yvat' (prisposoblját' by prisposáblivat') or vice versa (obsú^zivat' by obsu^zdát')? Besides present-day Russian, literary, journalistic and scientific publications from the 19th century have been examined in order to establish the dynamics of the linguistic development.